1977
DOI: 10.1346/ccmn.1977.0250302
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy in Relation to Deltaic Sedimentation Patterns of Desmoinesian Cyclothems in Iowa-Missouri

Abstract: AMtraet--Almost four decades of study of Desmoinesian strata of Middle Pennsylvanian age in southcentral Iowa and north-central Missouri have provided the stratigraphic control required to test the variation of clay mineralogy vertically and laterally within various paralic clay and shale facies. Local and regional variations in clay mineralogy within Desmoinesian strata are generally predictable and are in agreement with current knowledge of deltaic deposition. A principal environmental variation within a del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In well Uda-1, however, kaolinite decreases in abundance with depth (Table 2). This trend is probably indicative of a transition from nonmarine to marine facies (Brown et al, 1977), which supports the interpretation of a detrital orgin for kaolinite.…”
Section: Discussionsupporting
confidence: 82%
“…In well Uda-1, however, kaolinite decreases in abundance with depth (Table 2). This trend is probably indicative of a transition from nonmarine to marine facies (Brown et al, 1977), which supports the interpretation of a detrital orgin for kaolinite.…”
Section: Discussionsupporting
confidence: 82%
“…McMurtry and Fan (1975) demonstrate the elose resemblance between the elay mineralogy of downstream sediments from the Santa Ana river, South California, and of marine sediments deposited on the adjacent shelf in the N ortheastern Pacific Ocean (Fig. An exhaustive study performed by Brown et al (1977) on the Desmoinesian (middle Pennsylvanian) of Iowa-Missouri, USA, shows a elose relationship between elay suites and the chronologie and geographie evolution of a deltaic system. The seaward decrease of smectite could be determined either by a marine ingression in the lower course of the river, or a geochemical evolution into illite in K-rich sea water.…”
Section: 3 Marine Transgressionmentioning
confidence: 99%
“…The spacing of the 10 Å is in the range 10.3 to 10.5 Å. This type has been called "degraded illite" by Brown (1954); in the present sample it is considered to be a mixed-layer mineral of illite and montmorillonite, with a large proportion of illite layers.…”
Section: Mineral Compositionmentioning
confidence: 83%
“…Furthermore, such mixed-layer minerals can occur in shallower to considerably deeper levels, and also in young as well as old sediments, as long as an acidic chemical environment is maintained in sediments after deposition. Brown et al (1977) reported that degraded illite occurs in a mixed-layer state or as dioctahedral vermiculite in deltaic sediments of Middle Pennsylvanian age. Therefore, it is possible that the mixed-layer minerals in the lower section of Hole 439 are detrital.…”
Section: Discussionmentioning
confidence: 99%